The mediating effect of perceived employability on the relationship between protean career orientation, affective commitment and subjective career success among academics in Pakistan - Zafar, Junaid (2015)
The “new career” concepts found in the industrialized economies were studied since the implementation of career models in institutional environments having different social, cultural and political norms results in diverse patterns of career development. For carrying out the research, academics were chosen from Pakistan’s private sector universities. The private sector is commercialized and innovative, and thus fits well with the career concepts discussed in the study. To give support to the conceptual framework, the researcher has taken the protean career theory as the underpinning theory. For sampling purposes, proportionate stratified sampling has been adapted. Simple random sampling has been utilized to select the academics within each stratum. The sample was chosen out of a total population of 4,994 academics present within the 35 private sector universities located across the country. The questionnaire was distributed among individuals after obtaining permission from the universities. The researcher managed to collect data from 192 respondents with a response rate of 55%. After data input, it was cleaned of missing values, outliers, and tested for normality. Hypotheses were measured with structural equation modeling and confirmatory factor analysis in AMOS software. The researcher found statistically significant relationships between (i) protean career orientation and perceived employability (ii) affective commitment and perceived employability (iii) affective commitment and subjective career success. Statistically insignificant relationships have been found between (i) protean career orientation and subjective career success (ii) perceived employability and subjective career success. However, no mediation was observed as the relationship between perceived employability and subjective career success is insignificant. The current study is among the first on academics in private universities in Pakistan to establish relationships based on subjective career success rather than job satisfaction.